Identification of image object based on machine learning using tensorflow - Wempy Virgana Wempy; Apriansyah (International Journal Cister, 2022)
Image identification is one of the machine learning / artificial intelligence methods that can be used to detect an image quickly. This is one of the technological breakthroughs in science, especially in the field of computers. Object detection and recognition provides a new challenge on how to make machines detect objects automatically. Creating a machine learning model that has the function to determine the position and identify many objects in an image is still a major challenge in computer vision. Currently, many computing resources and intelligent algorithms can do this, but this feature can only be obtained by configuring a special machine to detect objects.